اضطراب الشحوم عند مرضى زرع الكلية - سعيد, حسين; درويش, علي; جديد, وليد (Latakia University Journal -Medical Sciences Series, 2019)
قمنا بدراسة عينة من 30 مريض أجروا زراعة كلية بفترات مختلفة وقمنا بمعايرة قيم اللبيدات: · الغلسريدات الثلاثية. · الكولسترول الكلي. · LDL كولسترول. · HDL كولسترول. بالطريقة المباشرة مع تحديد الأدوية الكابتة للمناعة عند كل مريض وكانت النتائج على الشكل الآتي: · كان اضطراب اللبيدات شائعاً وكان ارتفاع الشحوم الثلاثية الأكثر شيوعاً. · البروتوكولات التي تحوي الأزاتيوبرين + البردلون هي الأفضل والأقل تأثيراً في اضطراب الشحوم. · الاختلاطات القلبية الوعائية في دراستنا غير شائعة. We studied a group of 30 patients who had undergone kidney transplantation inside and outside of the country, and measured lipid values: Triglyceride Total cholesterol LDL. Cholesterol HDL cholesterol And we determined the immuno suppressive medications taken by patients. Results: Dyslipidemia was prevalent, and hypertriglyceride was the most prevalent. Protocols which contain (Azathioprine + Prednisone) are the best and have the least effect on dyslipidemia. Cardio–vascular complications were not common in our study.